III-nitride nanostructures: Emerging applications for Micro-LEDs, ultraviolet photonics, quantum optoelectronics, and artificial photosynthesis. (August 2022) - Wu, Yuanpeng; Liu, Xianhe; Pandey, Ayush; Zhou, Peng; Dong, Wan Jae; Wang, Ping; Min, Jungwook; Deotare, Parag; Kira, Mackillo; Kioupakis, Emmanouil; Mi, Zetian
Abstract: In this review article, we discuss the molecular beam epitaxy and basic structural, electronic, optical, excitonic, chemical and catalytic properties of III-nitride nanostructures, including nanowires, monolayer heterostructures, and quantum dots. Their emerging applications in ultraviolet, visible and infrared photonics, quantum optoelectronics, and artificial photosynthesis that are relevant for next generation mobile display, virtual/augmented reality, quantum communication, and energy, water, and environment sustainability challenges are presented.